Pelatihan Pembuatan Website untuk Promosi Desa Wisata di Desa Karang Bunga Kabupaten Barito Kuala - Wisnu Subroto; Melisa Prawitasari; Dewicca Fatma Nadilla; Muhammad Fadillah; Sri Dewi (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to increase the knowledge and skills of village officials and the tourism awareness group (Pokdarwis) of Karang Bunga village in creating and operating a website as a promotional medium for tourist villages. The method of implementing this service uses training, which includes lectures, demonstrations and discussions. This service evaluation instrument uses a questionnaire and descriptive analysis. The results of the service show that village officials and Karang Bunga Village Pokdarwis have the knowledge and skills to operate and manage the tourist village website well. The website that is owned can be used as a means of information in introducing the potential of the village so that it can become a tourist village.